SYNTHESIS OF NOVOLAC TYPE PHENOL FORMALDEHYDE OLIGOMERS - Givi Papava; Marina Gurgenishvili; Ia Chitrekashvili; Eter Gavashelidze; Nora Dokhturishvili (World Science, 2020)
Mixed novolac-type oligomers are synthesized in the melt on the base of oxibenzene and its alkilsubstituted. The content of dioxibenzene changes in the range of 0,1 – 0,5 mol. The influence of temperature and duration of the reaction of initial components, transformation has been studied.